(untitled) (Journal of Pharmaceutical Negative Results, 2022)
BACKGROUND: Caring is a holistic nursing that is useful to support the healing process of the client and how to establish relationships with the client's client and responsible for the client's condition. Caring is an attitude, respect, care, respect for each other which means giving more attention to others by learning the person's way of thinking and the way in which someone acts.AIM: The purpose of this study is: aims to determine the relationship of nurses caring attitudes to the level of patient care satisfaction in The Inpatient Room of a Hospital in JakartaMETHODS: This study used cross sectional. The sampling technique adopted a total sampling technique consisted of 90 respondents. Data were analyzed using Spearman rank test.RESULTS: The Spearman Rank test results show patients higher satisfaction when being cared for by nurses who have a high caring attitude. Statistical results show p 0.000 (<0.05) with R 0.656 meaning that there is a significant picture and a strong correlation between the caring attitude of nurses and the level of satisfaction of nursing care for patients in the inpatient room. Patients have high satisfaction as much as 81.1% (n=73) towards nurses who have a caring attitude. Patients have less satisfaction as much as 1.1% (n = 1) towards nurses who lack a caring attitude.CONCLUSION: Nurses who have a caring attitude in providing nursing services can increase patient satisfaction. Nursing management needs to create a program that can improve the caring attitude of nurses in providing services because caring is one of the factors of patient satisfaction. High patient satisfaction can provide an overview of the quality of hospital services. Nurses need to continue to hone a caring and professional attitude in providing nursing services.